Analisis Analisis Pola Pencarian Informasi Model David Ellis terhadap Kualitas Informasi Mahasiswa Aktif Organisasi Fakultas Ekonomi Bisnis Islam UINSU - Rumpaka, Putri Indah; Arianti, Novi; Dalimunthe, Astiana Sakinah; Rachellya, Tiara; Purwaningtyas, Franindya (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information seeking behavior is a specific activity or project that is carried out on an individual basis in order to find information that is required or desired in order to accomplish a certain goal. David Ellis' model of information searching behavior is the one that became the guiding principle in this study. Starting (awalan), Chaining (menghubungkan), Browsing (menelusur), Differentiating (pemilahan), Monitoring (memantau), and Extracting are the steps involved in the process of collecting the information (menggali). The purpose of this study is to comprehend various methods for collecting model ellis information that have been conducted at the Mahasiswa Aktif Organization of the Faculty of Economics and Business Islam at UINSU Medan in order to satisfy the need for this information in the course of instruction. The method that was used in this study was using a kualitatif method with case study alignment. The results show that some students come from internal campus organizations as many as 13 students (61.90%), Islamic economics majors have the highest percentage of other majors (61.90%), some students first conceptualize the information they want to trace (66.7%) , some students did information searches before looking at their bibliography as a reference source (76.2%), some students use the browsing stage by searching for information other than using google, namely by using print media and social media with the same presentation (38.09%), some students compared asking directly to the experts by looking at the development of information from new journal publications stated that they chose to ask their experts (57.1%), by continuing to search for information that was explored in depth to get information saturation points stated that 16 respondents (76.2%) agreed, re-checking the information that has been traced for medapa provide accurate data according to the needs of the informants (76.2%), closing access to the search when they have found the information they need (47.6%). Keywords: Information-seeking behavior, David Ellis Model